Human capital and firm performance: a contingent analysis - Roca-Puig, Vicente; Beltrán-Martín, Inmaculada; Segarra-Ciprés, Mercedes; Escrig Tena, Ana Belén; Bou-Llusar, Juan Carlos (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Growing interest has been shown in the degree to which investment in human capital contributes to firm performance, yet limited research attention has been paid to the contextual conditions that moderate this relation. This investment may be more beneficial in some contexts than in others. Specifically, this study examines how temporary work and organizational size affect the value of human capital. We carry out a comparative analysis of the impact of human capital on firm performance among small and large companies with high and low use of temporary employment. From a sample of 1,403 industrial Spanish companies, findings indicate that the impact of human capital on labor productivity and return on sales is moderated by temporary work and organizational size. The most beneficial context is represented by a large company with a high degree of human capital and a lower use of temporary employment.